2019
DOI: 10.1038/s41598-019-55189-5
|View full text |Cite
|
Sign up to set email alerts
|

VAS2870 and VAS3947 attenuate platelet activation and thrombus formation via a NOX-independent pathway downstream of PKC

Abstract: NADPH oxidase (NOX) enzymes are involved in a various physiological and pathological processes such as platelet activation and inflammation. Interestingly, we found that the pan-NOX inhibitors VAS compounds (VAS2870 and its analog VAS3947) exerted a highly potent antiplatelet effect. Unlike VAS compounds, concurrent inhibition of NOX1, 2, and 4 by treatment with ML171, GSK2795039, and GKT136901/GKT137831 did not affect thrombin and U46619-induced platelet aggregation. These findings suggest that VAS compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…It has been reported that the pan-NOX inhibitors VAS compounds (VAS2870 and its analog VAS3947) demonstrated a strong antiplatelet effect, inhibiting platelet aggregation by blocking PKC downstream signaling. The same finding was also reported in an animal model in which VAS compounds prevented thrombus formation [ 269 ]. Moreover, VAS2870 has been reported to be effective in counteracting amylin-induced reduction of endothelial responses in rat mesenteric arteries [ 270 ].…”
Section: New Therapeutic Approaches Targeted Endothelial Dysfunctisupporting
confidence: 85%
“…It has been reported that the pan-NOX inhibitors VAS compounds (VAS2870 and its analog VAS3947) demonstrated a strong antiplatelet effect, inhibiting platelet aggregation by blocking PKC downstream signaling. The same finding was also reported in an animal model in which VAS compounds prevented thrombus formation [ 269 ]. Moreover, VAS2870 has been reported to be effective in counteracting amylin-induced reduction of endothelial responses in rat mesenteric arteries [ 270 ].…”
Section: New Therapeutic Approaches Targeted Endothelial Dysfunctisupporting
confidence: 85%
“…Previous reports have shown that neither PDI deletion [ 6 ] nor Nox-1 deletion [ 27 ] increase bleeding time In line with our data, previous reports have shown that platelets from Nox-1 KO mice did not respond to collagen, whilst responses to thrombin were preserved [ 19 ]. It has also been reported that ML171 (also referred to as 2APT) does not affect platelet adhesion, nor does it inhibit aggregation induced by agonists other than collagen [ 18 , 40 ]. In contrast, one study reported that male Nox-1 KO mice presented defects in thrombin-stimulated platelets [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The platelet activation induced by collagen was associated with mitochondrial ROS generation and this ROS boosted platelet activation by regulation of different pathways. Therefore platelets are both source and target of ROS [ 35 , 37 , 38 , 39 ]. Additionally, mitochondrial ROS can directly induce inflammasome-mediated caspase-dependent platelet death [ 10 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In platelets, the mitochondria were the main source of ATP generation through oxidative phosphorylation and that ATP alone or its breakdown to ADP may activate platelets [ 41 ]. In this context, as an additional antiplatelet mechanism, MitoQ decreased the intraplatelet ATP content [ 37 , 42 , 43 ]. However, mitochondrial depolarization induced by MitoQ could affect platelet contractility and diminish clot stability [ 8 , 44 ].…”
Section: Discussionmentioning
confidence: 99%